Materials science and technology : a comprehensive treatment. Volume 7, Constitution and properties of steels / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol. editor : F. Brian Pickering - Pickering, F. Brian
Vol 7. Constitution and properties of steels in 1992